2020
DOI: 10.1017/s1355617720000272
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cognitive Markers to Identify Individuals at Increased Dementia Risk: Influence of Modifying Factors and Time to Diagnosis

Abstract: Objective: We investigated the extent to which combining cognitive markers increases the predictive value for future dementia, when compared to individual markers. Furthermore, we examined whether predictivity of markers differed depending on a range of modifying factors and time to diagnosis. Method: Neuropsychological assessment was performed for 2357 participants (60+ years) without dementia from the population-based Swedish National Study on Aging and Care in Kungsholmen. In the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…It is paramount to define novel approaches to the study of semantic memory, because this function is informative in clinical settings. Particularly, there is a strong body of evidence emerging from single-case studies ( Garrard et al, 2005 ; van Velzen and Garrard, 2008 ; Berisha et al, 2015 ) as well as large cohort longitudinal investigations ( Snowdon et al, 1996 ; Amieva et al, 2008 ; Gustavson et al, 2020 ; Payton et al, 2020 ) indicating that declining semantic memory is among the earliest neurocognitive changes observed along the timeline of Alzheimer’s disease, at a stage when no objective measurable alteration of episodic memory performance is yet detectable. Although this study is only exploratory in nature and needs to be replicated with larger cohorts, it points at the link between aspects of the DMN and semantic control as a potential major drive behind the link between SRO and item-level semantic features.…”
Section: Discussionmentioning
confidence: 99%
“…It is paramount to define novel approaches to the study of semantic memory, because this function is informative in clinical settings. Particularly, there is a strong body of evidence emerging from single-case studies ( Garrard et al, 2005 ; van Velzen and Garrard, 2008 ; Berisha et al, 2015 ) as well as large cohort longitudinal investigations ( Snowdon et al, 1996 ; Amieva et al, 2008 ; Gustavson et al, 2020 ; Payton et al, 2020 ) indicating that declining semantic memory is among the earliest neurocognitive changes observed along the timeline of Alzheimer’s disease, at a stage when no objective measurable alteration of episodic memory performance is yet detectable. Although this study is only exploratory in nature and needs to be replicated with larger cohorts, it points at the link between aspects of the DMN and semantic control as a potential major drive behind the link between SRO and item-level semantic features.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Higher education level is associated with better cognitive performance in several cognitive domains, 8 including memory, fluency, and executive function. As the association between cognitive performance and risk of Alzheimer's disease and related dementias is well established, 9 disparities between sexes in education are thus a potential pathway through which differences between sexes in the risk of Alzheimer's disease and related dementias are generated. 2 , 3 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Measures of SM are particularly important to the study of cognitive ageing. Findings from large cohorts of asymptomatic adults followed up longitudinally, in fact, have revealed that performance on a major SM test, the “Category Fluency Test” (CFT) (inclusive of its analogues, e.g., the “Isaacs Set Test”), is among the earliest predictors of future progression to Alzheimer’s disease ( Amieva et al, 2008 ; Payton et al, 2020 ). Conversely, a large body of evidence indicates that SM tends to be largely preserved and even improve with healthy ageing ( Nyberg et al, 1996 , 2003 ; Park et al, 2002 ; Verhaeghen, 2003 ; Rönnlund et al, 2005 ; Small et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%